Entre a crise de interpretação e a crítica: a hermenêutica como condição de possibilidade para o controle da internação-(des)medida - ALBUQUERQUE, Fernando da Silva (Universidade Federal do Pará, 2017)
The dissertation discusses the problem of discretion regarding the enforcement of socioeducationalmeasure of detention pursuant to Article 122 of the Statute of the Child andAdolescente (ECA). The scope is to understand the so-called interpretation crisis of the ECAand to presente under what conditions it is established in the field of enforcement of socioeducationalmeasure of detention. As results, the paper concludes that there is a need tocontrol judicial decisions in order to protect the rights and guarantees of adolescents and as away to overcome the crisis in the field of socio-educational justice. Chapter one explains thecontext of punishment of adolescents in Brazil. It indicates the permanence of judicialdiscretion concerning the enforcement of the measure, even after the entry into force of theECA and its supposedly objective criteria for detention of adolescents by the practice ofinfraction. In the second chapter, from decisions of the Superior Court Of Justice (STJ) sharessome discretionary possibilities in maintaining / or in determining the measure of detention.The paper explains, in view of the judicial reasoning, that these decisions contain arbitraryand subjective arguments to justify the enforcement of the measure. This type of reasoning isnot in accordance with the constitutional and democratic model of punishment. The finalchapter analyzes wheter hermeneutics is a condition of possibility to control the judicialdecision. It argues that the interpretation carried out by the judge is not an arbitrary processoof choosing sense and it justifies how its possible to think a democratic constraint for thejudicial decision, and it doesn’t imply a prohibition to interpret. It also presents therelationship between hermeneutics and legal dogmatic, debating as a hermeneutically situatedunderstanding of the interpretation process does not preclude other theoretical perspectives forthecontrol of decision.